Is pedagogical content knowledge (PCK) necessary for reformed science teaching? : Evidence from an empirical study - Park, Soonhye; Jang, Jeong-Yoon; Chen, Ying-Chih; Jung, Jinhong (Research in science education (Australasian Science Education Research Association), 2011)
This study tested a hypothesis that focused on whether or not teachers' pedagogical content knowledge (PCK) is a necessary body of knowledge for reformed science teaching. This study utilised a quantitative research method to investigate the correlation between a teacher's PCK level as measured by Parks' 2008 PCK rubric and the degree to which his/her classroom is reform-oriented as measured by the Reformed Teaching Observation Protocol (RTOP). Data included 33 instructional sessions of photosynthesis and heredity videotaped with 7 high school biology teachers. Each session was given a score on both the PCK rubric and RTOP by two independent raters. Results indicate that PCK score is significantly related to RTOP score in terms of both total score and sub-component scores. Implications for science teacher education and future research are discussed. [Author abstract, ed]